Development of Ethnoscience-Based Teaching Materials on Fluid Dynamics to Enhance Students’ Creativity - Hikmah, Nurul; Herayanti, Lovy; Gummah, Syifa’ul (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to develop ethnoscience-based physics teaching materials on fluid dynamics to enhance students’ creativity and learning outcomes. The research employed the 4-D development model (Define, Design, Develop, Disseminate) and was conducted up to the Develop stage, including needs analysis, design, expert validation, limited trials, and effectiveness testing. Validation results indicated that the materials were rated as very valid (88%) and valid (65%). A limited trial involving 34 students showed an improvement in conceptual understanding with a normalized gain (N-gain) of 0.61, categorized as moderate, while student responses were highly positive with an average score of 85.9 out of 100. The novelty of this research lies in the integration of local cultural knowledge, specifically the traditional sailboats of the Bima-Sape community, into physics instruction. This approach connects indigenous practices with scientific principles, producing culturally relevant and innovative learning materials that foster student engagement, contextual understanding, and creative thinking in physics education.